Influence of Immobilization of Bacterial Cells and TiO2 on Phenol Degradation - Park, Mee-Ree; Kim, Dong-Ju; Choi, Jae-Woo; Lim, Dae-Soon (Kluwer Academic Publishers, 2013)
We investigated the influence of immobilization of bacterial cells and photocatalytic material TiO2 on the degradation of phenol by conducting batch microcosm studies consisting of suspended, immobilized cells and immobilized TiO2 at various initial phenol concentrations (50-1,000 mgL(-1)). Results showed that both suspended and immobilized cells were concentration-dependent, exhibiting the increasing degradation rate with the concentration of up to 500 mgL(-1) above which it declined. The degradation rate of 0.39-3.47 mgL(-1)h(-1) by suspended cells was comparable with those of the literature. Comparison of the degradation rates between suspended, immobilized cells and immobilized TiO2 revealed that immobilized cells achieved the highest degradation rate followed by immobilized TiO2 and suspended cells due to the toxicity of phenol at the high concentration of 1,000 mgL(-1). This indicates that immobilization of bacterial cells or photocatalytic materials can serve a better alternative to offer the higher degradation efficiency at high phenol concentrations.